Management of the Conduction Independent Curriculum at Buddhist College: Case Study - Budiyanto, Budiyanto; Kabri, Kabri; Surya, Julia (Universitas Sarjanawiyata Tamansiswa, 2024)
Due to a fact that the concept is new for both learners and educators, there are several roles that must be taken into account when conducting MBKM. Many issues were discovered as a result of observations performed on several campuses, including the following: 1) Students from multiple campuses took part of learning implementation during the MBKM activity, but many of them were involved in these activities and had varied interests. 2) The phenomenon I discovered regarding the MBKM's actions as though it had not been managed. The researchers pose the research question,